2014
DOI: 10.1186/1756-0500-7-805
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of serous ovarian carcinoma using a multigene next generation sequencing cancer panel approach

Abstract: BackgroundHigh grade serous ovarian cancer is one of the poorly characterized malignancies. This study aimed to elucidate the mutational events in Malaysian patients with high grade serous ovarian cancer by performing targeted sequencing on 50 cancer hotspot genes.ResultsNine high grade serous ovarian carcinoma samples and ten normal ovarian tissues were obtained from Universiti Kebangsaan Malaysia Medical Center (UKMMC) and the Kajang Hospital. The Ion AmpliSeq™ Cancer Hotspot Panel v2 targeting “mutation-hot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…Consistently, TP53, BRCA1 , and BRCA2 were the most frequently altered genes in the TCGA ovarian serous cystadenocarcinoma data. Moreover, in line with other studies on the pattern of somatic mutations in human cancer genomes [ 15 , 25 ], we observed a higher rate of transitions than transversions. Even if metastatic tumor spread is a very complex process consisting of many different events, the mutational spectrum of our BM specimens was surprisingly simple, which is consistent with the findings of Beltrame et al, who reported that the genomic architecture of relapsed disease was less heterogenous than that of the primary disease [ 26 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistently, TP53, BRCA1 , and BRCA2 were the most frequently altered genes in the TCGA ovarian serous cystadenocarcinoma data. Moreover, in line with other studies on the pattern of somatic mutations in human cancer genomes [ 15 , 25 ], we observed a higher rate of transitions than transversions. Even if metastatic tumor spread is a very complex process consisting of many different events, the mutational spectrum of our BM specimens was surprisingly simple, which is consistent with the findings of Beltrame et al, who reported that the genomic architecture of relapsed disease was less heterogenous than that of the primary disease [ 26 ].…”
Section: Discussionsupporting
confidence: 92%
“…To date, most research efforts have focused on defining the molecular characteristics of primary OC [ 6 , 14 , 15 ]. Only very limited data are available on molecular aberrations in BM of OC [ 16 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mutation of TP53 gene is the most frequent genomic alteration of high-grade carcinomas, while KRAS and BRAF mutations are more likely encountered in low-grade ones 2,16,17 . In one study DNA derived from tumor was detected in the vaginas of 60% of patients with ovarian cancer with intact fallopian tubes and harbored the exact same TP53 mutation 18 .…”
Section: Resultsmentioning
confidence: 99%
“…Somatic mutations (substitutions, insertions, or deletions) were designed to amplify 207 amplicons covering ~2790 Catalogue of Somatic Mutations in Cancer (COSMIC) mutations from the 50 most commonly reported oncogenes and tumor suppressor genes (Ion Torrent™; Thermo Fisher Scientific, Inc.). Sequencing library preparation was performed according to the manufacturer's instructions (18,19). …”
Section: Methodsmentioning
confidence: 99%